Efficacy and safety of natalizumab in multiple sclerosis: interim observational programme results. Issue 11 (14th February 2014) - Butzkueven, Helmut; Kappos, Ludwig; Pellegrini, Fabio; Trojano, Maria; Wiendl, Heinz; Patel, Radhika N; Zhang, Annie; Hotermans, Christophe; Belachew, Shibeshih
Abstract : Background: Clinical trials established the efficacy and safety of natalizumab. Data are needed over longer periods of time and in the clinical practice setting. Objective: To evaluate long-term safety of natalizumab and its impact on annualised relapse rate and Expanded Disability Status Scale (EDSS) progression in patients with relapsing-remitting multiple sclerosis (RRMS). Methods: The Tysabri (natalizumab) Observational Program (TOP) is an open-label, multinational, 10-year prospective study in clinical practice settings. Results: In this 5-year interim analysis, 4821 patients were enrolled. Follow-up for at least 4 years from natalizumab commencement in 468 patients and at least 2 years in 2496 patients revealed no new safety signals. There were 18 cases of progressive multifocal leucoencephalopathy reported, following 11–44 natalizumab infusions. Mean annualised relapse rate decreased from 1.99 in the 12 months prior to baseline to 0.31 on natalizumab therapy (p<0.0001), remaining low at 5 years. Lower annualised relapse rates were observed in patients who used natalizumab as first MS therapy, in patients with lower baseline EDSS scores, and in patients with lower prenatalizumab relapse rates. Mean EDSS scores remained unchanged up to 5 years. Conclusions: Interim TOP data confirm natalizumab's overall safety profile and the low relapse rate and stabilised disability levels in natalizumab-treated patients with RRMS in clinical practice. Trial registration number: NCT00493298.